Pulmonary Hypertension in Pulmonary Langerhans Cell Granulomatosis - Matthias Held; Philipp Schnabel; Arne Warth; Berthold Jany (Case Reports in Medicine)
Introduction. Pulmonary Langerhans cell granulomatosis is a rare disease with a variable course. In pulmonary Langerhans cell granulomatosis pulmonary hypertension is frequent and has an independent prognostic impact. A vasculopathy which ist not related to ventilatory disturbance and fibrosis has been identified. An arteriopathy and even a venulopathy have been described. Due to this possible venulopathy vasodilators carry a significant risk for pulmonary congestion and edema. No drugs have been approved until now. Case Presentation. One female with PLCG developed severe PH four years after primary diagnosis of pulmonary Langerhans cell granulomatosis. Retrospective analysis of lung biopsies revealed an arterial vasculopathy at the time of primary diagnosis without clinical signs of PH at this time. Sildenafil led to a sustained improvement of hemodynamic features and exercise capacity. Conclusion. This paper underlines that patients with PLCG with an arterial vasculopathy-related PH might improve under sildenafil. Further trials addressing treatment of PH and vasculopathy are needed.